AN ANALYSIS OF ERRORS IN ENGLISH PRONUNCIATION:A CASE STUDY OF THE TENTH GRADE STUDENTS OF A HIGH SCHOOL IN BANDUNG - Sanusi, - (2010)
ABSTRACT The research entitled "AN ANALYSIS OF ERRORS IN ENGLISH PRONUNCIATION (A Case Study of the Tenth Grade Students of a High School in Bandung) is aimed at investigating pronunciation errors made by the participants in terms of categories of errors and discovering sounds that appear to be problems for them. The study was conducted using case study design in which the data were collected through a pronunciation test given to 62 students. The data derived were analyzed by referring to Haycraft's (1973) list of common types of errors. The result showed that among the seven categories of errors, the participants made five types of errors, namely type 1, there is any difference in pronunciation of the letter sound; type 2, sound appears the same as in the mother tongue but is not; type 3, the sound is alien; type 4, students find it hard to pronounce sounds embedded in cluster of consonants or vowels; and type 7, students do not expect sounds to change. Out of 54 test items, targeted phonemes in 31 numbers have less than 50% correct answers, making them categorized as problematic sounds.